2002
DOI: 10.1046/j.1537-2995.2002.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes and activation differences in platelet concentrates stored in plasma and additive solution

Abstract: With exception of baseline activation probably due to necessary handling procedures, platelets remain relatively unaltered and more stable in plasma in comparison to storage in PAS2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 40 publications
3
24
0
Order By: Relevance
“…Prolonged storage of PLT can lead to the so-called storage lesion which is characterized by a diminished adhesion to adhesive surfaces caused by a variety of factors such as the alteration of the vWF receptor and the inhibition of the Ca 2+ signaling pathway which can cause the clearance of affected PLT in the recipient [38]. The effect of storage has been investigated in several publications [30,39,40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged storage of PLT can lead to the so-called storage lesion which is characterized by a diminished adhesion to adhesive surfaces caused by a variety of factors such as the alteration of the vWF receptor and the inhibition of the Ca 2+ signaling pathway which can cause the clearance of affected PLT in the recipient [38]. The effect of storage has been investigated in several publications [30,39,40].…”
Section: Resultsmentioning
confidence: 99%
“…Fundamental research about the complex ultrastructure of PLT under resting and activated conditions has been done in the three last decades of the 20th century [20][21][22][23][24]. Only few publications can be found after 2000 [25][26][27][28][29] also using advanced methods such as special morphometric techniques [30] as well as highpressure cryofixation, and electron tomography [31].…”
Section: Analysis Of the Panorama Images Obtained From Pcmentioning
confidence: 99%
“…Increased P-selectin expression and structural changes have been suggested as possible mechanisms. 5,6 Whether such in vitro changes explain the inferior increments of PAS II PCs remains unclear. 8,9 To investigate the clinical relevance of the inferior CCI of PAS II PCs, we compared the incidence of bleeding, transfusion interval, red-cell concentrate usage, and the occurrence of transfusion failure, the latter also in relation to patient factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although in vitro studies showed significant differences suggesting inferior quality in metabolic, functional, and flow cytometric parameters in platelets stored in PAS II as compared with plasma, platelets stored up to 5 days in PAS II stay within the range of minimal quality requirements. [3][4][5][6] The correlation of these in vitro parameters with clinical efficacy is inconsistent. [7][8][9] One paired radiolabeled platelet survival study showed a significant decrease in both recovery as well as survival of PAS II PCs compared with plasma PCs and PCs stored in PlasmaLyte A (Baxter, Deerfield, IL).…”
Section: Introductionmentioning
confidence: 99%
“…Platelet additive solutions can be used as a substitute for plasma in order to recover plasma for other purposes, to avoid transfusion of large volumes of plasma to patients, to improve storage conditions, and to make possible photochemical treatment for viral inactivation of PCs [13]. Platelets remain relatively unaltered and more stable in plasma in comparison to storage in PAS-2 [14]. Currently, several platelet additive solutions for longterm platelet storage have been introduced, storing platelets in additive solution containing magnesium and potassium (PASIIIM) improves the functionality of the platelets, as measured by glycolysis, Ph, morphology, ATP and CD62 expression [15], and may allow a reduction of the amount of plasma required to be carried over to the final unit, facilitating some methods of viral inactivation and making available greater amounts of plasma for other needs [16].…”
Section: Discussionmentioning
confidence: 99%